Strengthening Counter-Radicalism Through Santri Discussion Group - Rindha Widyaningsih; Kuntarto; Muhamad Riza Chamadi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
The santri group discussion aims to strengthen the character of Pancasila and the santri knowledge about issues of radicalism and terrorism in order to avoid the radicalism ideology. The activity was held at the Darul Abror Purwokerto Islamic Boarding School with 50 participants. The community service method uses a combination of community education methods and group discussions. The activity was carried out in three sessions: providing educational material, in-group discussions, and inter-group discussions. In the first session, the method provides in-depth material on radicalism and Pancasila by the community service team. The method at the second session is in-group discussion. The second session's point was to improve the participants analytical skills in responding to radicalism and Pancasila issues. The method in the third session is inter-group discussion. The santri group discussion showed that the students in Darul Abror had increased knowledge about radicalism and terrorism and developed the character of Pancasila to prevent the threat of radicalism. Students sharpen hard skills through discussion activities in practice identification and analysis of problems and problem-solving. The development of participants' soft skills is a sense of respect for other people's opinions, tolerance, and culture of deliberation.